Vincenzo Appiani (1850-1932) nel contesto della scuola pianistica milanese (Gilgameš, 2019)
After an attempt to clarify the general concept of ‘piano school’ inboth its pedagogical and interpretative meaning, the article presentsthe most recent research results concerning the pianist, composerand pedagogue Vincenzo Appiani (Monza, 1850 – Milano, 1932),an outstanding representative of the Milanese piano tradition. Thepaper includes a biographical sketch of the musician and a firstreconstruction of his artistical and teaching activities in the widercontext of the new physiological achievements in piano technique- arm weight, wrist mobility asf. - and their influences in Italy at thebeginning of the XX c.